The Multilayer Nature of Molecular Gas toward the Cygnus Region - Zhang, Shiyu; Su, Yang; Chen, Xuepeng; Fang, Min; Yan, Qing-Zeng; Zhang, Shaobo; Sun, Yan; Wang, Xiaolong; Feng, Haoran; Ma, Yuehui; Zhang, Miaomiao; Zhuang, Zi; et al. (The Astronomical journal, 2024)
We study the physical properties and 3D distribution of molecular clouds (MCs) toward the Cygnus region using the MWISP CO survey and Gaia DR3 data. Based on Gaussian decomposition and clustering for 13 CO lines, over 70% of the fluxes are recovered. With the identification result of 13 CO structures, two models are designed to measure the distances of the molecular gas in velocity crowding regions. The distances of more than 200 large 13 CO structures are obtained toward the 150 deg 2 region. Additionally, tens of the identified MC structures coincide well with masers and/or intense mid-IR emission. We find multiple gas layers toward the region: (1) the extensive gas structures composing the Cygnus Rift from 700 pc to 1 kpc across the whole region; (2) the ∼1.3 kpc gas layer mainly in the Cygnus X South region; and (3) the 1.5 kpc dense filament at the Cygnus X North region and many cometary clouds shaped by Cygnus OB2. We also note that the spatial distribution of young stellar object candidates is generally consistent with the molecular gas structures. The total molecular mass of the Cygnus region is estimated to be ∼2.7 × 10 6 M ⊙ assuming an X-factor ratio X CO = 2 × 10 20 cm − 2 ( K km s − 1 ) − 1 . The foreground Cygnus Rift contributes ∼25% of the molecular mass in the whole region. Our work presents a new 3D view of the MCs' distribution toward the Cygnus X region, as well as the exact molecular gas mass distribution in the foreground Cygnus Rift.